(untitled) (Malaysian Management Journal, 1992)
This article investigates the issue of real versus nominal adjustment specifications in the Malaysian money demand function. Performance of both specifications was subjected to several tests, namely ; model specification ex-post forecasting ability and stability tests. Our results shows that under both specifications, the Malaysian money demand function for M1, M2 and M3 are not stable for the period 1962 – 1991. Our question is, does financial innovation during the period of 1979 – 1991 affected the stability of the Malaysian money demand function? A test on Gurley-Shaw hypothesis was done to answer the above question. However, our results suggest that financial innovation does not play a major role in affecting the Malaysian money demand function during the period under study. Nevertheless, the interest rate elasticities (for both short-run and long-run) has been declining over the period of 1979 – 1991, indicating the effectiveness of monetary policy as a policy tool.